Feasibility, reliability and validity of the Thai version of the Pediatric Quality of Life Inventory 3.0 cerebral palsy module - Pinailug Tantilipikorn (2018)
Background: Quality of Life (QOL) and Health-related Quality of Life (HRQOL) are now considered as necessary outcome measures for children with cerebral palsy (CP). Various reliable and valid condition-specific HRQOL tools are available for these children. One of these is Pediatric Quality of Life Inventory (PedsQL) 3.0 CP module which has been widely used and was translated to many languages. As no Thai version is available, the authors have completed this translation. Purpose: This study then aimed to investigate psychometric properties of the newly translated Thai PedsQL 3.0 CP module and to establish parent confidence in their ratings in the translated tool. Methods: Translation of the PedsQL 3.0 CP module was performed based on linguistic translation guidelines. Then, the psychometric properties of the Thai version were established. PedsQL 3.0 CP module was completed by children with CP and their parents or caregivers twice with 2-4 weeks. Results: Respondents were 97 parents or caregivers and 54 children. Minimal missing data were found. Acceptable internal consistency was supported except for Movement and Balance Scale (self-report). Intraclass correlation coefficients for parent proxy and self-report were good to excellent (0.684-0.950). Conclusions: The feasibility, reliability and validity of the translated tool were supported. © 2012 Springer Science+Business Media B.V.